SISTEMA DE DETECÇÃO DE INTRUSOS EM ATAQUES ORIUNDOS DE BOTNETS UTILIZANDO MÉTODO DE DETECÇÃO HÍBRIDO - CUNHA NETO, Raimundo Pereira da (2011)
The defense mechanisms expansion for cyber-attacks combat led to the malware evolution, which have become more structured to break these new safety barriers. Among the numerous malware, Botnet has become the biggest cyber threat due to its ability of controlling, the potentiality of making distributed attacks and because of the existing structure of control. The intrusion detection and prevention has had an increasingly important role in network computer security. In an intrusion detection system, information about the current situation and knowledge about the attacks contribute to the effectiveness of security process against this new cyber threat. The proposed solution presents an Intrusion Detection System (IDS) model which aims to expand Botnet detectors through active objects system by proposing a technology with collect by sensors, preprocessing filter and detection based on signature and anomaly, supported by the artificial intelligence method Particle Swarm Optimization (PSO) and Artificial Neural Networks.